2009
DOI: 10.2131/jts.34.305
|View full text |Cite
|
Sign up to set email alerts
|

A 55-week chronic toxicity study of dietary administered kojic acid (KA) in male F344 rats

Abstract: -A chronic toxicity study of kojic acid (KA) was performed using male F344 rats by dietary administration at concentrations of 0 (control), 0.5 and 2.0% for 55 weeks. Body weight gain was suppressed in the 2.0% group. The major hematological findings were decreased red blood cell (RBC) count and hematocrit (Ht) values at both 0.5 and 2.0%. In serum biochemistry, increased aspartate -hepatocytes and proliferation of bile ductules in both treatment groups, and hypertrophy of hepatocytes, granulomas and prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Male F344 rats were used in a 55-week toxicity dietary study of kojic acid. 93 The 7-week-old rats were divided into groups of 20 and received 0%, 0.5%, or 2.0% kojic acid (equivalent to 0, 227, or 968 mg/kg body weight/d, respectively). One week prior to treatment, rats received a single subcutaneous injection of 5 mL/kg saline.…”
Section: Carcinogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Male F344 rats were used in a 55-week toxicity dietary study of kojic acid. 93 The 7-week-old rats were divided into groups of 20 and received 0%, 0.5%, or 2.0% kojic acid (equivalent to 0, 227, or 968 mg/kg body weight/d, respectively). One week prior to treatment, rats received a single subcutaneous injection of 5 mL/kg saline.…”
Section: Carcinogenicitymentioning
confidence: 99%
“…The study concluded that the NOAEL of kojic acid was below 0.5% (227 mg/kg body weight/d). 93 Carcinogenicity studies are summarized in Table 5.…”
Section: Carcinogenicitymentioning
confidence: 99%
“…Some skin whitening agents used in cosmetics are known or suspected endocrine actives. Kojic acid has been demonstrated to interfere with either iodine organification or iodine uptake by the thyroid, resulting in altered thyroid functions [109,110]. Another compound used in skin whitening is resorcinol, which, as previously mentioned, has similar effect on thyroid function and hormone production.…”
Section: Skin Whitening Agentsmentioning
confidence: 97%
“…Although arbutin and kojic acid are popular in the cosmetic industry, several reports have found safety issues when these chemicals are used in pharmaceutical products [8][9][10]. Arbutin has remained in use in the cosmetic industry, but since 2001, other hydroquinones have not been used in skin-lightening formulations in the European Union [9].…”
Section: Introductionmentioning
confidence: 99%